Penatalaksanaan Fisioterapi pada Kasus Cervical Root Syndrome dengan Modalitas Transcutaneous Electrical Nerve Stimulation (TENS) dan Terapi Latihan di RSUD Bandung Kiwari - Neng Turina; Abdul Qudus (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Cervical Root Syndrome is a condition that occurs due to injury or pinching of the cervical spine due to continuous intervertebral foramen and is accompanied by neck pain that spreads to the shoulders, as well as the upper and lower extremities accompanied by tingling and weakness in the surrounding muscles. To determine the implementation of Physiotherapy in reducing pain, increasing muscle strength, increasing the Scope of Joint Movement and preventing contractures in cases of Cervical Root Syndrome using Transcutaneous Electrical Nerve Stimulation (TENS) and Exercise Therapy modalities. After 6 treatments using VAS, it showed a decrease in T1 to T6 silent pain with a value of 0, T1 to T6 pressure pain value with a value of 4 to 1, T1 to T6 movement pain value with a value of 6 to 2. The presence of Increased muscle strength by using MMT, namely flexion movements T1 to T6 with a score of 4 to 5, extension movements T1 to T6 with a score of 3 to 5, lateral flexion movements T1 to T6 with a score of 3 to 4. There is an increase in the range of motion of the joints with measurements using a Goneometer, namely cervical flexion and extension movements in the sagittal plane from T1 to T6 with an extension value of 25⸰ to a value of 45⸰, flexion movements with a value of 30⸰ to a value of 40⸰ calculated from 0o, lateral right and left cervical flexion movements moving at frontal plane from T1 to T6 with a right lateral flexion value of 30⸰ to a value of 45⸰, left lateral flexion movement with a value of 30⸰ to a value of 45⸰ calculated from a value of 0o, and right and left cervical rotation movements moving in the cervical rotation plane from T1 to T6 with a right rotation value of 40⸰ to a value of 50⸰, left rotation movement with a value of 40⸰ to a value of 50⸰ is calculated from a value of 0o. Transcutaneous Electrical Nerve Stimulation (TENS) can help reduce pain and reduce muscle tension, Exercise Therapy can increase muscle strength and increase joint range of motion and can help improve functional ability.